2022
DOI: 10.1002/brb3.2744
|View full text |Cite
|
Sign up to set email alerts
|

Genotype–phenotype characteristics of Vietnamese patients diagnosed with Charcot–Marie–Tooth disease

Abstract: Background: Charcot-Marie-Tooth (CMT) disease is one of the most common hereditary neuropathies. Identifying causative mutations in CMT is essential as it provides important information for genetic diagnosis and counseling. However, genetic information of Vietnamese patients diagnosed with CMT is currently not available. Methods:In this study, we described the clinical profile and determined the mutation spectrum of CMT in a cohort of Vietnamese patients with CMT by using a combination of multiplex ligation-de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…The development of NGS in Vietnam has allowed comprehensive genetic studies of multiple pathogenic conditions (M. D. Do et al., January, 2022 ; H. T. Nguyen et al., 2020 ; H.‐N. Nguyen et al., 2021 ; Nguyen‐Le, 2022 ). Analyzing the spectrum of PD‐related genes in different ethnicities is becoming important to the understanding of the genetic mechanism underlying the disease.…”
Section: Discussionmentioning
confidence: 99%
“…The development of NGS in Vietnam has allowed comprehensive genetic studies of multiple pathogenic conditions (M. D. Do et al., January, 2022 ; H. T. Nguyen et al., 2020 ; H.‐N. Nguyen et al., 2021 ; Nguyen‐Le, 2022 ). Analyzing the spectrum of PD‐related genes in different ethnicities is becoming important to the understanding of the genetic mechanism underlying the disease.…”
Section: Discussionmentioning
confidence: 99%
“…For example, it has been suggested that the Kinh Vietnamese population carries potentially unique genotype-phenotype associations. [30][31][32][33] For a country with approximately 100 million inhabitants and increasingly facing the challenges of T2DM, [34] genetic associations with T2DM in Kinh Vietnamese is important information that is worth studying. This study has some limitations.…”
Section: Tablementioning
confidence: 99%